2003
DOI: 10.1083/jcb.200303167
|View full text |Cite
|
Sign up to set email alerts
|

Centromere-associated protein-E is essential for the mammalian mitotic checkpoint to prevent aneuploidy due to single chromosome loss

Abstract: Centromere-associated protein-E (CENP-E) is an essential mitotic kinesin that is required for efficient, stable microtubule capture at kinetochores. It also directly binds to BubR1, a kinetochore-associated kinase implicated in the mitotic checkpoint, the major cell cycle control pathway in which unattached kinetochores prevent anaphase onset. Here, we show that single unattached kinetochores depleted of CENP-E cannot block entry into anaphase, resulting in aneuploidy in 25% of divisions in primary mouse fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
244
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(270 citation statements)
references
References 50 publications
23
244
1
2
Order By: Relevance
“…Consistent with previous studies (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004), cells depleted of CENP-E exhibit unaligned chromosomes close to spindle poles and misaligned chromosomes positioned between the metaphase plate and spindle poles at metaphase. Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous studies (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004), cells depleted of CENP-E exhibit unaligned chromosomes close to spindle poles and misaligned chromosomes positioned between the metaphase plate and spindle poles at metaphase. Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs.…”
Section: Discussionsupporting
confidence: 79%
“…Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs. Previous studies demonstrated that CENP-E binds to kinetochores and MTs and stabilizes their interaction, thereby contributing to silencing the mitotic spindle checkpoint (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004). CENP-E associates with and activates the mitotic checkpoint kinase BubR1, indicating that the spindle checkpoint is sensed through CENP-E kinetochore activity (Chan et al, 1998(Chan et al, , 1999Mao et al, 2003;Weaver et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BubR1 contains a carboxy terminal kinase domain that is absent in yeast Mad3p . BubR1 kinase activity is stimulated by binding to CENP-E Weaver et al, 2003], a kinetochore-associated microtubule motor [Wood et al, 1997] that functions in the SAC in Xenopus and mammalian cells Weaver et al, 2003]. Originally, BubR1 kinase activity was thought to be dispensable for SAC function in Xenopus egg extracts [Chen, 2002;Tang et al, 2001], but a recent study indicates that cells require a threshold level of CENP-E activated BubR1 kinase activity for SAC function and Mad2p recruitment to kinetochores .…”
Section: Protein Kinases and Phosphorylation In The Spindle Checkpointmentioning
confidence: 99%
“…68,69 Loss of CENP-E expression or altered function of CENP-E leads to inhibition of chromosome alignment during mitosis, resulting in the initiation of checkpoint activation and a delay in the completion of cell mitosis. 70,71 The inhibition of CENP-E using a potent and selective CENP-E inhibitor GSK923295A reportedly delayed the duration of cell mitosis, as characterized by the presence of lagging, nonequatorially aligned chromosomes associated with the spindle pole, and this was followed by apoptosis. 72,73 Several investigators have reported the efficacy of GSK923295A in nude mouse xenografts, 74 and its antitumor effects are the subject of current phase 1 clinical trials in patients with advanced solid tumors.…”
Section: Kinesin-7 Familymentioning
confidence: 99%